The Impact of Non-Economic Factors on Voluntary Tax Compliance Behavior: A Case Study of Small and Medium Enterprises in Vietnam - Thu Hien Nguyen (Economies, 2022)
One of the main reasons governments of developing countries, including Vietnam, face many difficulties in tax collection is taxpayers’ non-compliance with taxes. Therefore, the question for the governments of these countries is how to encourage taxpayers to comply voluntarily without having to resort to mandatory measures. This study examines non-economic factors affecting the voluntary tax compliance behavior of small and medium enterprises (SMEs) in Vietnam. The data used in the study were collected from the survey results of 339 tax accountants and managers at SMEs in some provinces and cities in Vietnam. The study data were processed with the statistical software SPSS 20 to test for Cronbach’s alpha, exploratory factor analysis, and linear regression analysis. The research results show that the possibility of tax inspection and audit, social norms, tax knowledge, personal norms, perception of the tax system’s fairness, and tax service quality has a significant influence on the voluntary tax compliance behavior of SMEs in Vietnam; of which, the possibility of tax inspection and audit has the strongest impact, and tax services quality has the weakest effect on the voluntary tax compliance behavior of these enterprises.